Single ionization of hydrogen molecules by fast protons as a function of the molecular alignment - Johnson, Nora G.; Mello, R. N.; Lundy, Michael E.; Kapplinger, J.; Parke, Eli; Carnes, K. D.; Ben-Itzhak, I.; Wells, E. (My University, 2005)
Relative cross sections for the 4MeV H++D2 (1Σ+g)→H++D+2(1sσ)+e− ionization process were measured as a function of the molecular alignment during the interaction. The angle between the molecular axis and the projectile was obtained by using a momentum imagining technique and isolating the events in which the D+2(1sσ) ions are excited to the vibrational continuum and subsequently dissociate. While anisotropic cross sections have been observed in the past for a number of collision processes involving both target electrons, the one electron process investigated here is isotropic within our experimental uncertainties.